Surgeon eye lens dose monitoring in catheterization lab: A multi-center survey: Invited for ECMP 2018 Focus Issue. (April 2019) - Betti, Margherita; Mazzoni, Lorenzo Nicola; Belli, Giacomo; Bernardi, Luca; Bicchi, Sara; Busoni, Simone; Fedele, David; Fedeli, Luca; Gasperi, Chiara; Gori, Cesare; Quattrocchi, Mariagrazia; Taddeucci, Adriana; et al.
Highlights: Cardiologists in catheterization procedures can receive high eye-lens equivalent doses. Individual eye-lens dosimetry is recommended for highly exposed workers. Accurate uncertainty assessment is needed in eye-lens dosimetry. Abstract: Purpose: To perform a multi-centre survey on the eye lens equivalent dose absorbed by primary interventionalist during catheterization procedures, using a personal dosimeter placed close to the eye lens. Methods: 15 different cardiologists working in 3 different centers, for a total of 5 operating rooms were enrolled. All of them were provided with a single thermoluminescent dosimeter positioned on the inner side of the temples of eyeglasses. The dose monitoring, performed on a two-months basis, started in 2016 and is still running. All dose measurements were performed by a ISO 17025 standard accredited dosimetry service thus providing certified uncertainties as well. Correlation of eye lens and wrist dose with KAP was also investigated. Results: A total number of 101 eye lens measurements were performed. Annual eye lens dose estimation was obtained for all 15 surgeons (mean, mode, range, standard deviation: 10.8, 8, 4.9–27.3, 5.6  mSv, respectively). Uncertainties on annual eye lens dose estimations ranged between 10% and 20%. No significant correlation was found between eye lens dose and KAP. Conclusions: Cardiologists involved in catheterization procedures may receive annual eye lens doses close to the ICRP 118 dose limit and thus individual monitoring with a dedicated dosimeter should be carried out. Uncertainty assessment play a relevant role in eye lens equivalent dose estimation to ensure not to exceed dose limit.